Service Quality of the Enforcement Offices: Comparison Between Existing and Pilot Application Offices of Turkey - ÖNAL, Erhan; ÇAVDAR, Ertuğrul; KIPÇAK, Emrullah (International Journal of Contemporary Economics and Administrative Sciences, 2019)
In this study, five quality dimensions of Servqual scale in terms of tangibles, reliability, responsiveness, assurance and empathy, as well as informing as a new dimension, the quality of service of the enforcement offices has been evaluated. The study included the evaluation and comparison of the quality of service offered by the current enforcement and Bankruptcy departments and the pilot enforcement departments established within the scope of the project carried out by the Ministry of Justice of the Republic of Turkey. In this context, enforcement offices in Van, Bitlis, Muş, Malatya and Gaziantep have been implemented. Application results show that the quality level of enforcement services is low. Although the applications in pilot regions have increased the quality of service, this increase has not been sufficient.